Revisiting The Post-Tsunami Aceh School: A Community-Based Evaluation Framework for Improving Build Back Better Projects - Fadhil, Muhammad Naufal; Putri, Aji Sofiana; Muslimin, Muhammad Fadli (UI Scholars Hub, 2025)
This study proposes a community-based evaluation framework to assess and improve the existing conditions of post-tsunami schools based on the occupants’ evaluations. Rapid, donor-driven reconstruction often defaults to ‘fit-for-all’ solutions that bypass community needs, resulting in facilities that are misaligned with local contexts. This project focused on Lampageu State Elementary School in Banda Aceh, Indonesia, which was reconstructed in 2009 by a German NGO after the 2004 tsunami. The project began by observing the school’s physical condition through the community engagement team, followed by a review and exploration of the school’s design needs with the school community. The community-based evaluation framework considers age as the basis for involvement, inviting 69 students to join the drawing workshops, 11 teachers, and 20 community members to join focus group discussion (FGD) sessions. Visual and narrative data from the community participation activities were analyzed thematically to reveal critical aspects to be improved. Based on the analysis, three essential design aspects for this evaluation framework are identified: physical enhancements, spatial experience, and functional safety, which were realized in a school redesign proposal. As a result, this study also provided a replicable framework through community participatory evaluation for improving the post-disaster design project. It expands the possibility of incorporating occupants’ perspective as a collective approach to translating community insights into design improvements.